Analisis Penetapan Harga Sewa Tenant Serta Biaya Maintenance Untuk Menentukan Pendapatan Laba Menggunakan ROI Dan ROE Pada PT Priamanaya Jasa Boga Tahun 2019-2022 - Ida Ayu Ningtyas; Nurlaela Eva Puji Lestari; Aris Hidayat (Journal of Islamic Economics and Finance, 2023)
Priamanaya Jasa Boga is a company in the field of leasing places to trade food and beverages which is often referred to as a food court. To find out whether tenant rental prices and maintenance costs affect the profit income of PT. Priamanaya Jasa is seen from ROI and ROE, The method used in this study is Descriptive Quantitative. The results of this study show that the analysis of tenant rental pricing and maintenance costs to determine profit income using ROI and ROE at PT. Priamanaya Jasa Boga in 2019-2022 can get a profit or benefited.